Satisfaction of women who used “breathable” Panty linersfor 75 days consecutively - Amaral, Rose Luce G; Giraldo, Paulo Cesar; Eleutério Junior, José; Gonçalves, Ana Katherine S; Beghini, Joziane; Gabiatte, José Roberto E (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: modern women develop 10 to 12 consecutive hours of work without having an appropriated genital hygiene, a fact that prompted the frequent use of panty liners in the intermenstrual period. Objective: check the satisfaction level of subjects after 75 days of wearing “breathable” panty liners (i. e., ones that allow movement of air and water vapor). Methods: implementation of a questionnaire to 54 women participants of a clinical trial for vulvar and vaginal ecosystem evaluation, who wore breathable panty liner (BPL) for 75 days to verify the satisfaction regarding the wearing thereof. The subjects were assessed for clinical exams and also answered two questionnaires related to work activity, vulvar discomfort (burning, irritation or pruritus), knowledge and wearing of breathable panty liners, their reasons for wearing them as well as satisfaction, being the former at the beginning and latter at the end of the study. Results: the women that attended the research were white and non-white in equal proportions, holding good educational background, body mass index close to 25 and with an average of 2.06 sexual intercourses per week, being away from home, on average 7.6 hours per day. Over 85% of subjects were previously familiarized with this type of product, albeit just 28.3% reported the habit of wearing panty liners throughout the intermenstrual period. Absence of irritation signs (vulvar hyperemia) occurred in 93.7% in Visit #2 (after 15 days of usage) and 93.2% of the women in visit #6 (after 75 days). Common complaints of vulvar discomfort (burning and irritation or pruritus) were not observed in 91.6% of the women in Visit #2 and 95.5% of the women in the end of study. These differences were not statistically meaningful (Fisher’s exact test with IC = 95%) between the visits. A complementary study indicates that these percentages are in line with the normal variations of women who do not wear panty liners. After 75 days of the study, 39 women (92.8%) said they felt more confident, protected and clean while wearing BPL. Conclusion: women who used “breathable” panty liners intermenstrual for 75 consecutive days, expressed high satisfaction and showed no clinically significant changes (hyperemia) or reported genital discomfort (burning and itching).Keywords: absorbent pads/panty liners, patient satisfaction, vulvitis, vulvovaginal candidiasis, vagina/microbiology, STDAmbulatório de Infecções Genitais (AIG) – Centro de Atenção Integral à Saúde da Mulher – Universidade Estadual de Campinas.1 Doutora pelo DTG/FCM/Unicamp, Médica do AIG.2 Professor Titular do DTG/FCM/Unicamp. Responsável pelo AIG.3 Doutor pelo DTG/FCM/Unicamp, Professor Adjunto do Departamento de Saúde Materno-infantil da Universidade Federal do Ceará.4Doutora pelo DTG/FCM/Unicamp, Professora Adjunta do DTG da Universidade Federal do Rio Grande do Norte.5Mestranda do DTG/FCM/Unicamp.6Professor Livre-docente do DTG/FCM/Unicamp.